Palladium/Azaphos-Catalyzed Asymmetric Suzuki–Miyaura Coupling - Jiang, Yanxin; Cheng, Kwai Wun; Zhang, Haoyang; Yang, Zhiping; Wang, Jun (Synthesis, 2023)
A palladium-catalyzed asymmetric Suzuki–Miyaura coupling is described with a unique monophosphine ligand, Azaphos. This method provides a new ligand framework that could be used in asymmetric Suzuki–Miyaura coupling reactions to prepare the axially chiral compounds.
Keywords: Suzuki–Miyaura coupling; azaphos; palladium; axial chirality